2021
DOI: 10.1111/fcp.12654
|View full text |Cite
|
Sign up to set email alerts
|

The contributions of metabolomics in the discovery of new therapeutic targets in Alzheimer's disease

Abstract: Alzheimer's disease (AD) leads to the progressive loss of memory and other cognitive functions. It is the most common form of dementia in the elderly and has become a major public health problem due to the increase in life expectancy. Although the detection of AD is based on several neuropsychological tests, imaging, and biological analyses, none of these biomarkers allows a clear understanding of the pathophysiological mechanisms involved in the disease, and no efficient treatment is currently available. Meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 95 publications
1
6
0
Order By: Relevance
“…Thus, it is crucial to compare these age-associated metabolic alterations with those occurring in AD for developing new therapeutic strategies for this age-associated, devastating dementia. A recent analysis of the literature on the whole central nervous system (Altine ´- Samey et al, 2021) showed that the pathways most significantly altered in AD are Arg biosynthesis and Ala/Asp/ Glu metabolism, whose metabolites were also confirmed to be significantly changed in our study (Figures 4 and S3B; Table S7).…”
Section: Discussionsupporting
confidence: 83%
“…Thus, it is crucial to compare these age-associated metabolic alterations with those occurring in AD for developing new therapeutic strategies for this age-associated, devastating dementia. A recent analysis of the literature on the whole central nervous system (Altine ´- Samey et al, 2021) showed that the pathways most significantly altered in AD are Arg biosynthesis and Ala/Asp/ Glu metabolism, whose metabolites were also confirmed to be significantly changed in our study (Figures 4 and S3B; Table S7).…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, most of them (i.e., taurine, glutathione, tyrosine, and glutamate) have been previously reported in several studies on metabolomics performed in biological samples from the CNS, both in animal models and in AD patients (Altine-Samey et al, 2021). However, the PLS-DA loadings with the larger absolute weights and the highest VIP scores were NAD and Nam (Supplementary Figure S1).…”
Section: Resultsmentioning
confidence: 83%
“…A metabolomic analysis of AD subjects revealed that increased alanine levels were found in the brain gray matter, while lower aspartate levels were found in the brain white matter. AD participants also had higher amounts of glutamate, and neuronal death was linked to the dysregulation of the glutamatergic system [ 49 ]. Changes in glutamate metabolism can impact GABA metabolism because glutamate decarboxylase converts glutamate to GABA, which can be derived from GABA [ 50 ].…”
Section: Discussionmentioning
confidence: 99%